Good and bad testosterone - Huhtaniemi, Ilpo (Academic Press, 2023)
"Good and Bad Testosterone is a unique reference to understand and learn about the biology and psychophysical aspects of this hormone. Unlike most other hormones, testosterone regulates not only the biological functions of the body but also many psychological functions. This wide spectrum of effects, influencing nearly all biological and behavioral features of a males, makes testosterone particularly interesting. This book takes a historical approach to understanding testosterone. It provides is a comprehensive description of the functions of testosterone and its role in determining the biological, medical, psychological, behavioral, and cultural features of the male sex/gender and the male/female differences. Sex/gender issues are of great interest for a wide readership, including the general public and experts from various disciplines."